2012
DOI: 10.3892/or.2012.1824
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of first-line erlotinib in elderly patients with advanced non-small cell lung cancer

Abstract: Abstract. TaRceva LUng cancer Survival Treatment (TRUST)was an open-label, phase IV study of advanced non-small cell lung cancer (NSCLC). Patients failing or unsuitable for chemotherapy or radiotherapy received erlotinib 150 mg/day until progression. We examined a subpopulation of elderly patients (≥70 years) receiving first-line erlotinib (n=485) in TRUST. In this subpopulation, disease control rate (n=356 with best response data available) was 79% (vs. 69% for the overall TRUST population; P<0.0001); median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A cardiotoxicity study revealed that sunitinib treatment resulted in mitochondrial damage and myocardial apoptosis in mice and cultured rat cardiomyocytes (5). Erlotinib has been demonstrated as a safe and well-tolerated treatment for NSCLC (6)(7)(8)(9), with no cases of myocardial infarction reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…A cardiotoxicity study revealed that sunitinib treatment resulted in mitochondrial damage and myocardial apoptosis in mice and cultured rat cardiomyocytes (5). Erlotinib has been demonstrated as a safe and well-tolerated treatment for NSCLC (6)(7)(8)(9), with no cases of myocardial infarction reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…In a subpopulation of elderly patients (≥70 years) receiving first-line erlotinib ( n  = 485) in TRUST [43], the disease control rate was 79 %, median PFS was 4.57 months, and MST was 7.29 months. A total of 87 subpopulation patients (18 %) had an erlotinib-related adverse event (AE); 4 % had a ≥3 grade erlotinib-related AE.…”
Section: Personalized Therapy By Egfr Mutations In Advanced Nsclcmentioning
confidence: 99%
“…In most studies, patients received erlotinib as first-line treatment [ 27 29 ] or the treatment line was not defined [ 30 , 31 ]. Four studies included exclusively Asian patients [ 27 , 31 33 ], who are known to have a better outcome with EGFR-TKI treatment compared to Caucasian patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%